Electronic processes in NO dimerization on Ag and Cu clusters: DFT and MRMP2 studies. Issue 1 (31st October 2018) - Takagi, Nozomi; Nakagaki, Masayuki; Ishimura, Kazuya; Fukuda, Ryoichi; Ehara, Masahiro; Sakaki, Shigeyoshi
Abstract : Experimentally observed NO dimerization on Cu and Ag surfaces is surprising because binding energy of NO dimer is very small in gas phase. MRMP2, MP2 to MP4, CCSD(T), and DFT studies of NO dimerization on Ag2 and Cu2 clusters disclosed that the CCSD(T) method could be applied to this reaction on Ag2 and Cu2 unlike NO dimerization in gas phase which exhibits significantly large nondynamical electron correlation effect. Charge‐transfer (CT) from Ag2 and Cu2 to NO moieties plays important role in NN bond formation between two NO molecules. This CT considerably decreases nondynamical correlation effect. Also, the DFT method could be applied to this NO dimerization, if appropriate DFT functional is used; all pure functionals examined here and most of the hybrid functionals underestimated the activation barrier ( E a ), while only ωB97X provided E a similar to CCSD(T)‐calculated value. NO dimerization on similar Cu2 and Cu5 needs moderately larger E a than those on Ag2 and Ag5, because frontier orbital participating in the CT exists at lower energy in Cu2 and Cu5 than in Ag2 and Ag5 . The E a decreases in the order Ag2 >> Ag38 > Ag7 ∼ Ag5 and the reaction energy (Δ E ) is positive (endothermic) in Ag2 but significantly negative in Ag38, Ag7, and Ag5, indicating that various Ag clusters could be effective for NO dimerization except for Ag2 . The decreasing order of E a and increasing order of exothermicity are attributed to increasing order of the frontier orbital energy of Ag2 < Ag38 < Ag7 ∼ Ag5 . © 2018 Wiley Periodicals, Inc. Abstract : NO dimerization on Ag and Cu clusters differs very much from that in gas phase. The nondynamical electron correlation effect is very small and the reaction easily occurs with nearly no barrier and significantly large exothermicity on these clusters.